2019
DOI: 10.14814/phy2.14244
|View full text |Cite
|
Sign up to set email alerts
|

H19 is not hypomethylated or upregulated with age or sex in the aortic valves of mice

Abstract: Epigenetic dysregulation of long noncoding RNA H19 was recently found to be associated with calcific aortic valve disease (CAVD) in humans by repressing NOTCH1 transcription. This finding offers a possible epigenetic explanation for the abundance of cases of CAVD that are not explained by any clear genetic mutation. In this study, we examined the effect of age and sex on epigenetic dysregulation of H19 and subsequent aortic stenosis. Cohorts of littermate, wild‐type C57BL/6 mice were studied at developmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…74 Although we obtained our pVICs from castrated male pigs, our hVIC observations corroborate sexual dimorphisms observed in pVICs, suggesting that cellular sex differences exist despite hormone status. AVS mouse models also corroborate sex differences in human disease, 75 indicating that cells and tissues from relevant animal sources may be useful tools for understanding sex-specific AVS progression. Together, our results support the observation that cells and tissues of different sexes have distinct regulatory networks that may give rise to sexually dimorphic phenotypes.…”
Section: Discussionmentioning
confidence: 74%
“…74 Although we obtained our pVICs from castrated male pigs, our hVIC observations corroborate sexual dimorphisms observed in pVICs, suggesting that cellular sex differences exist despite hormone status. AVS mouse models also corroborate sex differences in human disease, 75 indicating that cells and tissues from relevant animal sources may be useful tools for understanding sex-specific AVS progression. Together, our results support the observation that cells and tissues of different sexes have distinct regulatory networks that may give rise to sexually dimorphic phenotypes.…”
Section: Discussionmentioning
confidence: 74%
“…In the same manner, significantly higher serum expression levels of H19 were observed among patients who developed SSc before 14 years of age ( p = 0.018). This was also seen in mice models where younger mice had a higher average H19 expression than older mice [ 60 ]. Further investigations of these findings seem relevant, particularly with the fact that younger patients with SSc ≤30 years frequently present with more disseminated disease [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 78%
“…Hadji et al, reported that increased levels of H19 in CAVD lead to an abnormal mineralisation of the aortic valve [ 124 ]. Reducing NOTCH1 signalling in valve interstitial cells increases the expression of genes such as RUNX2 and BMP2 which play a pro-osteogenic role [ 124 , 145 ]. A similar mechanism of action of H19 has been documented in studies of neurogenesis after ischemic stroke.…”
Section: Notch1-related Lncrnas and Other Diseasesmentioning
confidence: 99%